PENILAIAN VITALITAS DAN KUALITAS TAPAK DENGAN FOREST HEALTH MONITORING (FHM) DIBAWAH TEGAKAN JAMBU METE (ANACARDIUM OCCIDENTALE L.) DI DESA NUSANIPA, KECAMATAN TANJUNG BUNGA, KABUPATEN FLORES TIMUR. - Luron, Yohanes A. P.; Pellondou, Mamie E.; Riwu Kaho, Norman P.L.B. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted in Tanjung Bunga District, East Flores Regency. This study aims to assess the vitality and quality of the cashew nut. The indicators observed were tree damage, canopy condition, cation exchange capacity and soil pH. The aims of this study were (1) to determine the health condition of the cashew tree and (2) to find out what factors influence it. The samples used were tree stands and soil samples, the technique of determining the sample was using cluster plots. Analysis of the data used is to calculate the index value of tree damage and canopy conditions and perform soil analysis to assess soil conditions. The results of this study showed that the health condition of the cashew stand at the tree level was in the poor category and the canopy condition in the medium category. The value of the quality of the site shows the cation exchange capacity (CEC) has a high value and the pH of the soil has a slightly acidic value. The influencing factors are Livestock, Plant Pest Organisms (OPT), environment, fire and limited water.